PEMANFAATAN KULIT PISANG HIJAU LUMUT (Musa x Paradisiaca L.) SEBAGAI BAHAN AKTIF MASKER PEEL OFF DAN SABUN MANDI ANTIBAKTERI - Rita, W.S.; Suirta, I.W.; Asih, I.A.R.A.; Sahara, E.; Santi, S.R. (Buletin Udayana Mengabdi; Vol 22 No 2 (2023): Buletin Udayana Mengabdi, 2023)
Hijau Lumut banana peel (HLBP) is useful as an active ingredient in masks and antibacterial bath soap. The purpose of the service is to provide training on making peel-off masks and antibacterial bath soap to women in Wongaya Gede Village, Penebel, Tabanan. The mask was made by dissolving carboxymethyl cellulose (CMC) and gelatin with hot water to form a gel, then other ingredients were added such as propylene glycol as a moisturizer, vitamin E as a skin protectant, and HLBP extract. All ingredients were homogenized until a gel-like mask was formed. Soap was produced by mixing coconut oil (VCO), olive, castor, and milk with a base (NaOH). Glycerin and honey were then added to keep the skin soft. The training was held on Thursday, 11 August 2022. This training can help women in using banana peels as masks and antibacterial soaps, so they can be used for entrepreneurship. Keywords: Banana, Antibacterial, Mask, Soap, Wongaya Gede